A Synthesis Elements of Professional Vocational Education Teachers in Thailand - Tawica Mekarkakorn, ถวิกา เมฆอัคฆกรณ์; Suwanna Narkwiboonwong, สุวรรณา นาควิบูลย์วงศ์ (Dusit Thani College Journal, 2018)
This research aimed to synthesize the attributes of professional vocational education teachers in order to explain the elements of this particular group of teachers in Thailand. The methods used were documentary research and content analysis. Study in 38 handbooks and articles for vocational education profession between A.D. 1949-2014. Content validity was conducted by using concepts and theories in vocational education, as well as related research and documents. According to the results, there are 3 elements that make up professional vocational education teachers in Thailand: work competency, behavior, and student quality of learners.